Design And Implementation Of Multiband RFID System For Hypermarket e-Payment System - Nalinggam, Renuka (2019)
The bill creation method that applied in hypermarkets is time-consuming and customers have to wait for a long time to get their bill. This research focuses on finding a solution to reduce the waiting time at bill counter using embedded multiband RFID technology. Passive RFID technology and ZigBee wireless module characteristics were studied and multiband RFID system (EPARFID) system was developed to be used to obtain experimental data to analyze WSN performance and RFID characteristics. The EPARFID system was embedded with two mechanisms which are the 915 MHz RFID passive system and 2.45 GHz ZigBee based active RFID. The EPARFID system performance was tested and compared with the standalone ZigBee module by focusing on common performance indicators such as Communication range, Throughput Evaluation, Latency, Self-Healing and Data Collision. Set of RFID characteristics experiments have been performed in this research and some essential characteristics of RFID technology are successfully found. It was found that the optimum distance between tag and reader is 0.7 m for LOS and 0.3 m for NLOS. Based on the investigation, it is successfully validated that RFID technology does not need LOS in detecting the passive tags. It also found that the relative dielectric permittivity of the materials that being used in the experiment is giving significant effects on EPARFID performance. Materials with lower relative permittivity show consistence performances compared to materials with higher relative permittivity. A combination of experimental data with analytical EM models improves the extrapolation of RFID read-rates in a given environment. The model approach is a step towards developing a robust methodology to predict RFID read-rates on complex set of materials or standard packaging materials (SPM). The results obtained from the proposed prediction modeling of read rate based on the Friis free space equation through a quantification of uncertainties provides new insights on the nature of tag read rates. Furthermore, the confirmation of the closeness of the proposed model approach with the EPARFID system experimental data establishes the validity of the proposed modeling approach.